A segmental root development as an unusual healing response to the revitalization of mandibular second premolar - Sadaf Tamanna; Aaliya Rehman; Rajendra Kumar Tewari; Surendra Kumar Mishra (Wolters Kluwer Medknow Publications, 2022)
A 15-year-old patient reported persistent pain in the left mandibular second premolar (#35) following a traumatic bite 3 months ago. Clinical examination revealed a fractured central cusp suggestive of dens evaginatus. Intraoral periapical radiograph revealed an immature permanent tooth with a periapical radiolucency. A diagnosis of pulp necrosis with symptomatic apical periodontitis was made. The tooth was treated according to the revised guidelines of regenerative endodontic procedure by the American Association of Endodontics. The follow-up evaluation revealed a complete resolution of periapical pathology. A detached radiopaque tissue was appreciated at the 12-month follow-up. It resembled a broken root tip at the 24-month follow-up. Both the main root body and disjointed root tip developed independently. A cone-beam computed tomography evaluation at the 36-month follow-up confirmed the segmented development of the apical root tip.